High Temperature Reproducible Preparation of Mg2Si Films on (001)Al2O3 substrates Using RF Magnetron Sputtering Method. Issue 1642 (16th May 2014) - Katagiri, Atsuo; Ogawa, Shota; Shimizu, Takao; Matsushima, Masaaki; Akiyama, Kensuke; Funakubo, Hiroshi
ABSTRACT: A RF magnetron sputtering method was used to prepare Mg2 Si films at 300-400 o C on (001) Al2 O3 substrates from a Mg disc target with Si chips. Mg deposition was not detected at 400 ° C from a pure Mg disc target without Si chips due to the high vapor pressure of Mg. However, the amount of Mg deposition increased with the increase in Si/(Mg+Si) area ratio of the target surface together with the increase of the Si deposition. The obtained films had a stoichiometric composition of Si/(Mg+Si)=0.33 that consisted of the well crystalline Mg2 Si single phase regardless of Si/(Mg+Si) area ratio of the target surface. This showed the existence of a "process window" against supply ratio of Si/(Mg+Si) for Mg2 Si single phase films with a stoichiometric composition. This is considered to be due to the vaporization of the excess Mg prepared under the Mg excess condition as reported by Mahan et al. for Mg2 Si films prepared at 200 ° C by ultra-high vacuum evaporation.